Symptomatic Subclinical Hypothyroidism Treated with Homoeopathy: Case Reports - Bhattacharya, Pulakendu; Giri, Shashi; Ghosh, Baishakhi; Banerjee, Abhiram (Homœopathic Links, 2020)
Subclinical hypothyroidism (SCH) is a condition where serum thyroid-stimulating hormone (TSH) level is high, but the T3 and T4 are within normal level. SCH carries a risk of cardiovascular diseases or progression to overt hypothyroidism. Treatment becomes more necessary in case of older age groups and in females. Two cases of SCH treated with individualised homoeopathic medicine are presented and the improvement was significant showing reduction in the TSH levels with overall improvement in health.
Keywords: subclinical hypothyroidism; thyroid-stimulating hormone; Ignatia; individualisation; Homoeopathy